1984
DOI: 10.1038/bjc.1984.3
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistological study of testicular germ cell tumours using two different monoclonal antibodies against placental alkaline phosphatase

Abstract: Summary Using two monoclonal antibodies directed against placental alkaline phosphatase (H17E2 and D20L) the immunohistological staining of testicular germ cell tumours was compared with that of a wide range of normal and malignant tissues. All seminomas and malignant teratomas tested gave strong positive labelling with H17E2 but were either negative or only patchily positive with D20L. Neither antibody gave any positive reaction on the normal tissues tested. All other malignancies were negative with both anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…However, our detailed immunohistochemical and previous biochemical analysis (Hole & Stern, 1988) shows that the antigen recognised is novel and distinct from the Psubunit of HCG or recently reported urinary gonadotrophin peptide (UGP) (Kardana et al, 1988), PLAP (Johnson, 1984), trophoblast-leukocyte common antigen (Stern et al, 1986) and those which react with mAb 18A/C4 and 18B/A5 (Loke et al, 1986). Some of (Epenetos et al, 1984), were almost all negative using mAb 5T4. The one case that showed some positivity was a seminoma containing syncytiotrophoblast giant cells, admixed with embryonal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…However, our detailed immunohistochemical and previous biochemical analysis (Hole & Stern, 1988) shows that the antigen recognised is novel and distinct from the Psubunit of HCG or recently reported urinary gonadotrophin peptide (UGP) (Kardana et al, 1988), PLAP (Johnson, 1984), trophoblast-leukocyte common antigen (Stern et al, 1986) and those which react with mAb 18A/C4 and 18B/A5 (Loke et al, 1986). Some of (Epenetos et al, 1984), were almost all negative using mAb 5T4. The one case that showed some positivity was a seminoma containing syncytiotrophoblast giant cells, admixed with embryonal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…The scFv is directed against the tumour-associated antigen human placental-like alkaline phosphatase (PLAP), which is an isoform of the placental alkaline phosphatase. This antigen is expressed on many tumours, such as ovarian and testicular, as well as some bladder and head and neck cancers (Epenetos et al, 1984;Iles et al, 1994). The antibody used is the well-studied H17E2 Epenetos et al, 1986).…”
mentioning
confidence: 99%
“…This suggests that although PLAP is expressed by all types of germ cell tumours of the testis (Epenetos et al, 1984) only seminomatous tumours actually release PLAP into the bloodstream. Elevated levels of PLAP (above 0.20.D.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown (Epenetos et al, 1984) that placental alkaline phosphatase (PLAP) as detected by monoclonal antibody H17E2 is expressed on the surface membrane of most testicular germ cell tumour cells. H17E2 immunoassay of sera of patients with testicular cancer as reported in the accompanying paper (Tucker et al, 1985) showed elevated PLAP levels in patients with seminoma.…”
mentioning
confidence: 99%